Pengaruh Aspek Moneter Dan Fiskal Terhadap Inflasi Indonesia - Nurhayun Fatmayani; Jihad Lukis Panjawa (Jurnal Ekonomi Pembangunan, 2021)
The economic stability of a country can be seen from the inflation rate. This study aimed to analyze the influence of monetary and fiscal aspects on inflation and the most effective policies for inflation problems in Indonesia, using time series data for 2010-2019 and the VECM model. The result showed that the money supply and tax revenue influence inflation and that there is a one-way causality relationship. The interest rate variable has not control inflation. The result of the causality test also shows that interest rate does not affect the money supply variabel, and tax revenue variables do not affect the money supply variable. The explanation of the estimation result of the VECM model generally shows that there is a long-term relationship and short-term relationship of each variable.